External Fixator–Assisted Reduction of Distal Femur Fractures: A Technical Trick. Issue 5 (May 2021) - Shymon, Stephen J.; Ulitto, Joseph; Barei, David P.; Sirkin, Michael S.; Reilly, Mark C.; Adams, Mark R.
Abstract : Summary: Restoration of anatomical alignment while preserving the soft-tissue envelope around the fracture site remains a challenge during distal femur fracture fixation. Although the lateral distal femoral locking plate allows surgeons to achieve adequate bony stability, their application has been associated with malalignment leading to inferior outcomes. We propose a biologically friendly, percutaneous technique that sequentially reduces and aligns distal femur fractures with an anterior external fixator before definitive fixation with a lateral distal femoral locking plate. Abstract : Supplemental Digital Content is Available in the Text.